PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB UNTUK MEMBANTU SISWA MEMPERSIAPKAN UJI KOMPETENSI PEMBUATAN SURIMI - Eka Alimatus Sa'diyah; Sri Handayani; Dewi Nur Azizah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The purpose of this study is 1) to determine the feasibility of website-based learning media on the competency test material for making surimi, 2) knowing the results of students' cognitive training on the competency test material for making surimi using website-based media, 3) knowing the results of students' cognitive training on the competency test material for making surimiusing e-modules, 4) knowing the differences in the results of students' cognitive training after using website-based media with e-modules. The method used is the ADDIE model and is implemented using the Intact-Group Comparison design in class XII majoring in Agroindustry at SMK N 1 Cibadak with cognitive aspects as research factors. The results showed that the website-based learning media was declared